Spinal cord injury enhances lung inflammation and exacerbates immune response following exposure to LPS - Berk, Bradford C.; Pereira, Amanda; Vizcarra, Velia Sofia; Pröschel, Christoph; Hsu, Chia George (Frontiers in Immunology, 2025)
IntroductionThe severity of spinal cord injury (SCI) is closely tied to pulmonary function, especially in cases of higher SCI levels. Despite this connection, the underlying pathological mechanisms in the lungs post-SCI are not well understood. Previous research has established a connection between disrupted sympathetic regulation and splenocyte apoptosis in high thoracic SCI, leading to pulmonary dysfunction. The aim of this study was to investigate whether mice with low-level SCI exhibit increased susceptibility to acute lung injury by eliciting systemic inflammatory responses that operate independently of the sympathetic nervous system. MethodsHere, we employed T9 contusion SCI and exposed mice to aerosolized lipopolysaccharide (LPS) to simulate lung inflammation associated with acute respiratory distress syndrome (ARDS). Twenty-four hours post-LPS exposure, lung tissues and bronchoalveolar lavage (BAL) fluid were analyzed. ResultsLPS markedly induced proinflammatory gene expression (SAA3, IRG1, NLRP3, IL-1beta, MCP-1) and cytokine release (IL-1beta, IL-6, MCP-1) in SCI mice compared to controls, indicating an exaggerated inflammatory response. Infiltration of Ly6G/C positive neutrophils and macrophages was significantly higher in SCI mice lungs post-LPS exposure. Interestingly, spleen size and weight did not differ between control and SCI mice, suggesting that T9 SCI alone does not cause spleen atrophy. Notably, bone-marrow-derived macrophages (BMDMs) from SCI mice exhibited hyper-responsiveness to LPS. DiscussionsThis study demonstrated an increase in lung inflammation and immune responses subsequent to low-level T9 SCI, underscoring the widespread influence of systemic inflammation post-SCI, especially pronounced in specific organs like the lungs.